THE PERCEPTION OF FISH FARMER TOWARD UTILIZATION OF EX QUARRY SAND LAND FOR AQUACULTURE BUSSINESS AT UJUNGBATU VILLAGE UJUNGBATU DISTRICT ROKAN HULU REGENCY RIAU PROVINCE - Elsa Christyn Gultom; Ridar Hendri; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conduted on September 2015 in the Ujungbatu Village,District of Ujungbatu that located in Regent of RokanHulu Riau Province. Thisresearch was determined purposively with survey method. The respondents wastaken by census amounting to 12 people. The purpose of this researchwere1)toknowfish farmers characteristics in the Ujungbatu Village, 2) to know perceptionsof fish farmer of ex quarry sand land utilization for aquaculture business, 3) and toknow relationship fish farmer characteristics between perception of fish farmerthe ex quarry sand land utilization used the Spearman Rank CorrelationCoefficienttest.The results of this research indicated that the fish farmer perceptions of theex quarry sand land utilization as a whole was in the category of "Good Enough"in the middle categories, with a score of 2.065. Internal factors which havesignificant affect to respondents perception in Ujungbatu Village are age andeducation and did not have significant affect to respondents perception areincome, family members, and experience of aquaculture bussiness.The results relationship between characteristics to perception, that are :correlation between age to fish farmer perceptions is very significant (0,040≤ rs,),correlation between education to fish farmer perceptions is very significant(0,032≤ rs,), correlation between family members is not significant (0,521 > rs),correlation between income to fish farmer perceptions is not significant (0,375 >rs), and correlation between experience of aquaculture bussiness to fish farmerperceptions is very significant (0,056 ≤ rs).Keywords:Perception, Ujungbatu Village, Ex quarry sand